Factors affecting the efficacy of a vinegar trap for Drosophila suzikii (Diptera; Drosophilidae). (4th April 2013) - Basoalto, E.; Hilton, R.; Knight, A.
Abstract: Drosophila suzukii, Matsumura, is a relatively new pest in the United States attacking a variety of fruit crops. Studies were conducted to develop a standardized, economical trap for monitoring. Laboratory bioassays found that flies were attracted to dark colours ranging from red to black. Similarly, fly catches in 237‐ml plastic 'spice' jars with ten 0.48‐cm holes and baited with apple cider vinegar were significantly higher in jars with red or black than white caps. The use of an alternating set of three, horizontal red, black and red bands ('Zorro' trap) significantly increased fly catches compared with the use of all‐red or all‐black strips. This increase was associated with a significantly higher proportion of flies first landing on the side near the openings of the trap instead of on the cap with the 'Zorro' trap compared with the other traps. Laboratory data were used to develop a predictive model to define total fly capture as a function of trap colour/colour pattern, cumulative area of entry holes and the length of the trapping portion of the trap. Total fly catches by the 'Zorro' trap were compared with other red and clear plastic traps in five field trials conducted in several cultivated and uncultivated sites. Comparisons included a commercial red‐capped 200‐ml trap with two 0.63‐cm holes, an all‐red spice jar with ten 0.48‐cm holes and clear and red 473‐ml and clear 946‐ml plastic cups with six or ten 0.48‐ or 0.63‐cm holes. The model was successfully validated, suggesting that performance of cup traps can be predicted based on a few characteristics. The current 'Zorro' trap did not catch most of the flies among trap designs, but showed some advantages, including the durability and potential to recycle the plastic, small size, commercial availability and its greater selectivity for D. suzukii than the other traps tested.